IMPROVING STUDENTS’ SPEAKING ABILITY USING GUESSING GAMES IN SMP AL FALAH DELTASARI SIDOARJO - Ana Christanti (FKIP Universitas Islam Jember, 2016)
This research aimed at applying teaching spoken descriptive text using guessing games in eight grade students of SMP Al Falah Deltasari Sidoarjo. It described how to teach spoken descriptive text using guessing games and reported the improvement of students’ speaking ability on learning process and test score. This Classroom Action Research (CAR) had 8-4 class students as subject of the research. The researcher worked together with two collaborators to collect the data using observation sheet, video recording, field-note and questionnaires. The research gained quantitative data; students’ score on spoken descriptive text presentation and qualitative one; description on teacher and students’ activities in teaching learning process and students’ reflection on the use of games in their class. The research finally found that the use of guessing game in the class improved students speaking activities, reduced stress, increased self-confidence; as students were eager to speak up, and gave more chance to every student on practicing speaking. The use of games also motivated students to improve their vocabularies. Students were excited and enjoyed the class. The improvement on students speaking ability was also found in spoken descriptive text scores. It was significant in performance area of content, grammar and vocabulary. The researchers, however, did not concern on the improvement on pronunciation performance area. It was, therefore, suggested to be observed by other researchers. Key words: Spoken descriptive text, Guessing games, improvement.